Plant Responses and Tolerance to Salt Stress: Physiological and Molecular Interventions 2.0 - Hasanuzzaman, Mirza; Fujita, Masayuki (International journal of molecular sciences, 2023)
Environmental problems are pervasive and significantly impact a variety of plant species, which are affected by two broad types of conditions: abiotic and biotic stress [...].Environmental problems are pervasive and significantly impact a variety of plant species, which are affected by two broad types of conditions: abiotic and biotic stress [...].